Biomechanical behavior of cancellous bone on patellofemoral arthroplasty with Journey prosthesis : a finite element study - Castro, André (2012)
Isolated patellofemoral (PF) arthritis of the knee affects approximately 10% of the population in general. Patellofemoral arthroplasty (PFA) is a bone conserving solution for patients with isolated PF degeneration. Typical failure mechanisms of PFA include growing tibiofemoral arthritis or loosening of components. The implant loosening can be related to bone resorption, or fatigue-failure of bone by overload. This work aimed to determine the structural effects of the implantation of PF prosthesis on femur cancellous bone, because studies on the state of strain/stress on PFA are very limited. The hypothesis here considered lies in the fact that the nature and magnitude of PF cyclic loads generate strain/stress levels at bone that exceeds the fatigue strength of these materials. The Journey PFJ was the prosthesis taken into consideration in this study. The finite element (FE) method is used to model, simulate and analyze the effect PF loads on cancellous bone. These FE models were previously validated with prior experimental results. The implanted model was simulated with two different cement-cancellous bone interface conditions, with the aim of representing well-fixed and loosening scenarios, for the prosthesis. From the global results produced, in the well-fixed scenario, a strain decrease on cancellous bone was noticed, which can be associated with bone resorption risk. In the loosening scenario, when the cement layer becomes inefficient, a large increase of cancellous bone strain was observed, which can be associated with bone fatigue-failure risk. These insights given by strain changes suggest a vulnerability of the femur after PFA.